2005
DOI: 10.1007/s00265-005-0024-9
|View full text |Cite
|
Sign up to set email alerts
|

Kin-related spatial structure in brown bears Ursus arctos

Abstract: International audienceKin-related social structure may influence reproductive success and survival and, hence, the dynamics of populations. It has been documented in many gregarious animal populations, but few solitary species. Using molecular methods and field data we tested: (1) whether kin-related spatial structure exists in the brown bear (Ursus arctos), which is a solitary carnivore, (2) whether home ranges of adult female kin overlap more than those of nonkin, and (3) whether multigenerational matrilinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
156
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(171 citation statements)
references
References 36 publications
14
156
1
Order By: Relevance
“…Recently, through measuring interpopulation differences of microsatellite allele frequencies and relatedness structure, Zhan et al (2007) found a female-biased dispersal pattern of giant pandas at a fine scale-Wanglang Nature Reserve. This female bias is different from that of many other mammals (Lawson Handley and Perrin 2007), including other bears for which data are available (Proctor et al 2004;Støen et al 2005;Costello et al 2008). This finding was based on a fine scale, and larger-scale studies are now needed.…”
Section: Introductioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Recently, through measuring interpopulation differences of microsatellite allele frequencies and relatedness structure, Zhan et al (2007) found a female-biased dispersal pattern of giant pandas at a fine scale-Wanglang Nature Reserve. This female bias is different from that of many other mammals (Lawson Handley and Perrin 2007), including other bears for which data are available (Proctor et al 2004;Støen et al 2005;Costello et al 2008). This finding was based on a fine scale, and larger-scale studies are now needed.…”
Section: Introductioncontrasting
confidence: 49%
“…This is especially true across long distances or complicated topography (Turchin 1998;Manel et al 2003) which, with natural and/or anthropogenic landscape heterogeneity, hampers animal movement (Manel et al 2003). Recent researches into spatial genetic structure (i.e., nonrandom spatial distribution of genetic variation) have shown that this methodology can be used to elucidate movement patterns (Peakall et al 2003;Fredsted et al 2005), especially for threatened or elusive species (Støen et al 2005;Goossens et al 2006;Hammond et al 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Dahle and Swenson (2003a) found that home range sizes of both male and female brown bears were inversely related to population density in Scandinavia. Støen et al (2005) found that overlap of home ranges in female brown bears in Scandinavia was positively related to relatedness, indicating that brown bears recognize kin and tolerate kin more than non-kin. These results, in addition to the results in this study, suggest that brown bears might be more territorial than previously thought, and that density is regulated by social interactions.…”
Section: Discussionmentioning
confidence: 93%
“…The inverse density-dependent dispersal probably contributes to an increased spatially heterogeneous abundance of brown bears in the landscape. Because brown bears are spatially structured in matrilinear assemblages (Støen et al 2005), this might lead to a spatial variation in population dynamics within the population and among matrilines, as seen in other species and theoretical studies (Jost and Brandl 1997;Lecomte et al 2004;Ims and Andreassen 2005).…”
Section: Discussionmentioning
confidence: 98%
“…As we focused our analyses on these areas, we determined that these individuals were also significantly more related to each other than expected by chance. Since females are philopatric, and are expected to form areas of high relatedness (Støen et al 2005), it is difficult to draw conclusions regarding population structure of females. However, in areas where males appear to be structured, females show similar patterns thereby further suggesting a barrier to gene flow, and thus population structuring for all individuals.…”
Section: Discussionmentioning
confidence: 99%